Anxiety Level Of Ssb Kijang Pinrang Players After Experiencing Injury - Sahabuddin Sahabuddin; Muhammad Ishak; Arman Fadillah (Jurnal Olahraga Kebugaran dan Rehabilitasi (JOKER), 2024)
This research is descriptive. The method used is a survey. The data collection technique uses a questionnaire. The population in this study were 25 SSB Kijang Pinrang players. Sampling in this study was carried out by purposive sampling. The criteria for determining this sample include: (1) willing to be a research sample, (2) present at the time of data collection, and (3) having experienced an injury. Based on these criteria, 15 players were met. The data analysis technique used quantitative descriptive analysis presented in the form of a percentage. The results of the study showed that the level of anxiety of Kijang Pinrang players after experiencing an injury was in the category of "very low" at 6.67% (1 person), "low" at 33.33% (5 people), "sufficient" at 26.67% (4 people), "high" at 26.67% (4 people), and "very high" at 6.67% (1 person).